Magnetic moment investigations of epitaxial magnetite thin films - ARORA, SUNIL KUMAR; SHVETS, IGOR (AMERICAN INSTITUTE OF PHYSICS, 2008)
In this report, we provide an x-ray magnetic circular dichroism (XMCD) study for 100?nm thick epitaxial magnetite (Fe3O4) films on MgO (001) and Al2O3 (0001) substrates. For XMCD, we recorded the surface sensitive total electron yield and the bulk sensitive transmission spectra. From the analysis of the XMCD data, we find an increased Fe spin moment (10% larger) at the surface of the film on MgO (100) with respect to the corresponding bulk value of the film. Surface and bulk spin moments of the film on Al2O3(0001) are almost equal. For both films, the bulk orbital to spin moments ratio increases from zero at 70?K to 0.03?0.04 at 300?K. For Fe3O4/MgO (001), the surface orbital to spin moment ratio behaves similarly to the bulk value, while the orbital to spin moments ratio is increased at the Fe3O4/Al2O3 (0001) surface to 0.06. The observed differences between films grown on MgO and Al2O3 are explained within the framework of differences in mismatch strain experienced by the films.
Journal of Applied Physics
52nd Annual Conference on Magnetism and Magnetic Materials
PUBLISHED
Tampa, Florida, USA
Keywords: Atomic, molecular and chemical physics; thin films